The Roles of Selectin Ligands and Innate Immune Responses in Modulating Resistance to Intracellular Bacterial Infections in Murine Hosts with Altered Immunity - Agbayani, Gerard Patrick (Université d'Ottawa / University of Ottawa, 2018)
Listeria monocytogenes (LM) and Salmonella enterica serovar Typhimurium (ST) are intracellular bacterial pathogens that cause invasive disease in immune-altered individuals, including the immunocompromised and pregnant women. The mechanisms that modulate innate immunity to intracellular infection, particularly during pregnancy, are not well-understood. Functional selectin ligands play critical roles in leukocyte recruitment during inflammation. Increased control of LM infection in functional selectin ligand-deficient (FtDKO) mice is associated with increased levels of circulating innate immune cells, despite defective leukocyte migration compared to WT mice. Adoptive transfer of WT and FtDKO bone marrow (BM) cells to irradiated WT and FtDKO recipients demonstrates that BM reconstitution and the increased neutrophil phenotype of FtDKO mice is independent of functional selectin ligand expression within the host environment. Thus, functional selectin ligand deficiency enhances inherent innate immune resistance to intracellular infection. We then examined the impact of pregnancy-associated immunological changes on maternal susceptibility to intracellular infections. ST infection in pregnant mice results in profound systemic infection, increased fetal loss and enhanced serum and placental expression of pro-inflammatory cytokines. Pregnant mice showed decreased ratios of pro-inflammatory Th17 cells relative to anti-inflammatory regulatory T cells (Tregs) when compared to non-pregnant mice during infection. Functional inactivation of Tregs in vivo restored control of infection and normal Th17-to-Treg ratios, and reduced fetal loss. These indicate that modulation of Th17 and Treg responses impacts maternal and fetal protection from ST infection. Lastly, we examined the roles of type I interferons (IFNs) in modulating innate immunity to intracellular infections during pregnancy. Type I IFN receptor deficiency (IFNAR-/-) enhances immunity to LM and ST in the non-pregnant state by limiting pathogen-induced leukocyte death. We show that pregnant IFNAR-/- mice infected with LM retain increased protection from infection relative to WT controls. In contrast, protection conferred by IFNAR deficiency against ST infection in the non-pregnant state is abrogated during pregnancy. Distinctive maternal responses to LM and ST are associated with differential regulation of leukocyte distribution and cytokine expression in maternal systemic and/or placental compartments. Taken together, modulation of key mechanisms involved in leukocyte recruitment, immune-regulation and cytokine signaling impact host susceptibility to intracellular infections.
Keywords: Selectin Ligands; Intracellular Infection; Listeria; Salmonella; Innate Immunity; Pregnancy; Type I Interferon; Th17 Cell; Regulatory T Cell; Cytokines